The Grammar Errors in Mandarin Speech Texts By Class XI IBB Students of SMA Nurul Jadid Paiton Probolinggo - Ruhil Qudsiyah; Karina Fefi Laksana Sakti; Tiksno Widyatmoko (Universitas Negeri Malang, 2025)
Grammar is the science of sentence construction. There are significant differences between Indonesian grammar and Chinese grammar in sentence structure. Students often face difficulties in composing speech texts according to Chinese grammar rules. This study aims to identify the forms of grammatical errors in Chinese speech texts and describe the factors that cause these errors made by students of class XI IBB SMA Nurul Jadid. This research method is descriptive qualitative with instruments in the form of speech text documents from 20 students. The results showed several forms of grammatical errors that often occur, such as the placement of adverbs of place, verbs, vocabulary usage, and punctuation. Factors causing these errors include lack of practice, limited mastery of vocabulary, and the habit of using Indonesian order patterns.